1998
DOI: 10.1021/la9805443
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Inorganic Polyanions along a Langmuir Film:  A Brewster Angle Microscopic Study

Abstract: Interactions of large inorganic polyanions along a positively charged Langmuir film of dimethyldioctadecylammonium bromide were studied by Brewster angle microscopy (BAM). Because of their large size (>10 Å) and high refractive index, their adsorption along the organic monolayer induces an increase of the interface reflectivity and can be directly monitored by BAM. Furthermore, they strongly modify the morphology of the film and a coexistence of three phases (gaseous, liquid expanded, and liquid condensed) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
6
17
0
Order By: Relevance
“…The sloping plateau of the LE/LC transition in the isotherm may be induced by large kinetic effects related to the strong repulsion forces between polar heads. Other authors have already observed such effect by BAM experiments [20,21]. They reported that a DODA monolayer at low surface pressure was in a homogeneous LE phase.…”
Section: Doda Monolayer On Pure Watermentioning
confidence: 77%
See 2 more Smart Citations
“…The sloping plateau of the LE/LC transition in the isotherm may be induced by large kinetic effects related to the strong repulsion forces between polar heads. Other authors have already observed such effect by BAM experiments [20,21]. They reported that a DODA monolayer at low surface pressure was in a homogeneous LE phase.…”
Section: Doda Monolayer On Pure Watermentioning
confidence: 77%
“…The DODA monolayer has already been characterized at the air-water interface by ellipsometry [17], attenuated total reflection [18], reflection spectroscopy [19], and Brewster angle microscopy [20,21], and recently, some grazing incidence Xray diffraction experiments have been reported [22]. Initially, the DODA monolayer is characterized on water in order to establish a reference under the same experimental conditions as those used for the spontaneous polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The coexistence of LC and LE phases in a DODAB monolayer over a wide range of surface pressure is well known in the literature [16]. The LC microdomains, disk-like or irregularshaped, appear dispersed in a homogeneous and isotropic LE phase.…”
Section: Bam Imagesmentioning
confidence: 88%
“…The shape and size of these domains as well as their textural features depend on the chemical structure of the amphiphiles and the monolayer state is determined by the surface pressure and temperature. The observation of DODAB monolayers by BAM has shown the bright domains dispersed in a black matrix forming from low surface pressures, as well as a variety of morphologies, induced by adsorption of inorganic polyanions from the subphase [16].…”
Section: Introductionmentioning
confidence: 99%